2016
DOI: 10.4081/monaldi.2010.310
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive effects of supplemented essential amino acids in patients with severe COPD and sarcopenia

Abstract: EAAs supplemented, but not patients assuming placebo, progressively improved all baseline variables overtime. In particular, at T12 of EAAs supplementation, body weight (BW) increased by 6 Kg (p = 0.002), FFM by 3.6 Kg (p = 0.05), plasma lactate decreased from 1.6 micromol/l to 1.3 micromol/l (p = 0.023), PaO2 increased by 4.6 mmHg (p = 0.01), physical activity increased by 80% (p = 0.01). Moreover, the score for cognitive dysfunction improved from 19.1 scores to 20.8 (p = 0.011), while the SRGQ score also imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 58 publications
2
60
0
Order By: Relevance
“…From a clinical perspective, this study confirms data obtained in previous investigations carried out in patients with COPD [8,9] or with chronic heart failure [10] who were supplemented with the same amino acid formula, at the same dose used in the present study. EAAs should not be intended as a substitute for Rehab whenever possible.…”
Section: B) Eaas and Quality Of Lifesupporting
confidence: 91%
See 2 more Smart Citations
“…From a clinical perspective, this study confirms data obtained in previous investigations carried out in patients with COPD [8,9] or with chronic heart failure [10] who were supplemented with the same amino acid formula, at the same dose used in the present study. EAAs should not be intended as a substitute for Rehab whenever possible.…”
Section: B) Eaas and Quality Of Lifesupporting
confidence: 91%
“…Despite the high prevalence in COPD subjects [48,49], cognitive dysfunction is often underestimated in clinical practice, and an altered cognition may reflect the pulmonary dysfunction [48] and/or hyposaturation of oxygen [50,51]. The improvement of saturation of oxygen can contribute to reduce cognitive dysfunction [8], while EAAs may directly influence cognition as several amino acids are precursors of brain neurotransmitters [8].…”
Section: B) Eaas and Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Included RCTs measured the effects of ET (n=10),1524 activity counseling (n=15),2540 health monitoring (n=1),41,42 pharmacological treatment (n=3),4345 nutritional interventions (n=2),4648 oxygen therapy (n=4),14,4951 urban walking circuits (n=1)52 and integrated disease management (n=1)53 on PA levels in COPD. PA counseling was delivered either in a center-based setting (n=9),2527,29,30,3234,39 through phone calls (n=3)31,36,37 or by internet-mediated approaches (n=3) 35,38,40.…”
Section: Resultsmentioning
confidence: 99%
“…15,24 None of the studies included in the meta-analyses had blinded the assessors or the therapists from study groups. One study of essential amino acid (EAA) supplementation46,47 reported an increase in steps favoring the intervention arm at 3 months (577.6 steps, P =0.02); however, insufficient sample size details prevented ES calculations (Table S1). Important increases in daily steps were also reported in a crossover RCT in favor of the once-daily long-acting beta agonist, indacaterol 150 μg,45 compared to placebo at 3 weeks (0.32 [0.02–0.63]; Table S1).…”
Section: Analysis Of Included Interventionsmentioning
confidence: 99%